Patient experiences of their current asthma care and their views toward providing support for patients with asthma in community pharmacy: A Qualitative study - Aseel Mahmoud; Rachel Mullen; Peter E. Penson; Charles Morecroft (Elsevier, 2024)
Background: An estimated 300 million people live with asthma globally. In England, a significant percentage live with poorly controlled asthma symptoms. Community pharmacists might be able to play a role in filling gaps in asthma care as they have the expertise and are in regular contact with patients with long term conditions. This study described patients' experiences of the management of their asthma in the general physician (GP) practice and community pharmacy settings and explored patients' views on providing support for them in community pharmacy. Method: This is a descriptive qualitative study. Thirteen adult asthma patients were recruited from a GP practice in the Northwest of England. Semi-structured qualitative interviews were conducted face-to-face or by telephone. The interviews were recorded, transcribed and analysed using a thematic analysis approach. Ethics approval was obtained before the study commenced and all participants gave informed written consent to participate. Results: We identified challenges in the current asthma care provided to patients with asthma including lack of continuity of care, inability to book an appointment and other experienced differences in the quality of asthma care provided to them and/or access to annual asthma reviews across different GP practices. Additionally, there is lack of awareness of services provided in community pharmacy. These challenges along with having comorbidities alongside asthma may negatively affect asthma patients' engagement with their asthma appointments and their behaviour toward their asthma. Conclusions: Patients showed trust in community pharmacists same as other HCPs to support them with their asthma care. Patients thought that being provided with regular asthma care including reviews in community pharmacy might be a suitable approach to respond to patients' needs and preferences in terms of their asthma management because of ease of access to community pharmacy. Pharmacists could be involved in the provision of community pharmacy-based asthma interventions that involve more than inhaler technique education. Further research should focus on developing structured approaches for asthma patient education that can be implemented consistently in the context of community pharmacy in England.